Investigation on NiWO4/PANI composite as an electrode material for energy storage devices. (26th October 2021) - Rajkumar, S.; Gowri, S.; Dhineshkumar, S.; Merlin, J. Princy; Sathiyan, A.
Abstract : NiWO4 /PANI was synthesized by an in situ chemical oxidative polymerization route. Incorporation of NiWO4 in a PANI matrix rendered high specific capacitance and salient morphological features. Abstract : With the fast exhaustion of fossil fuels, the need for new energy storage materials to meet the world's massive energy demand has increased tremendously. Inorganic components with conducting polymer based materials for supercapacitors (SCs) have seen significant research breakthroughs in recent years. Herein, we report an efficient material of a NiWO4 /PANI composite, synthesised successfully via a polymerization route. The composite was characterized by different physico-chemical techniques. NiWO4 /PANI exhibited a unique morphology with more redox sites, which enhanced the electrochemical performance. Moreover, the NiWO4 /PANI electrode delivered a high specific capacity ( C s ) of 854 C g −1 at a current density of 1 A g −1 and a considerable capacitance retention of 91.6% even after 5000 GCD cycles at 2 A g −1 . The advantage of the high conductivity of PANI and short ion transport channels of NiWO4, combined with the synergistic factor of NiWO4 and PANI, resulted in an improved specific capacity. Also, this work puts forward an alternate energy storage material to fabricate high performance SCs.